Investigation of criminal offences against property: typical investigative situations and problems of applying specialised knowledge - R. L. Stepaniuk; V. O. Husieva (Bulletin of Kharkiv National University of Internal Affairs)
During the period of the martial law regime, the legal system of Ukraine has undergone certain changes, as well as quantitative and qualitative indicators of crime. This has led to the fact that some criminal offences have become a significant part of the crime structure and have therefore become the focus of professional attention of law enforcement agencies. These include, inter alia, criminal offences against property, including theft, robbery, assault, extortion, fraud, misappropriation, embezzlement or misappropriation of property through abuse of office, and more. This has highlighted the need to ensure effective counteraction to such criminal offences.